2018
DOI: 10.1097/ccm.0000000000003429
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response Syndrome as Predictor of Poor Outcome in Nontraumatic Subarachnoid Hemorrhage Patients

Abstract: Objectives: Subarachnoid hemorrhage is a life-threatening disease associated with high mortality and morbidity. A substantial number of patients develop systemic inflammatory response syndrome. We aimed to identify risk factors for systemic inflammatory response syndrome development and to evaluate the role of systemic inflammatory response syndrome on patients’ outcome. Design: Retrospective observational cohort study of prospectively collected data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…The previous definitions, which included the SIRS criteria, were less specific and did not clearly discriminate sepsis from a systemic inflammatory response due to noninfectious causes, such as an SAH. Two retrospective studies [24, 25] found associations between the SIRS burden and worse outcomes in SAH, with SIRS incidence ranging from 69 to 85%. Although present in 82% of our patients, SIRS was not associated with a poor outcome after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The previous definitions, which included the SIRS criteria, were less specific and did not clearly discriminate sepsis from a systemic inflammatory response due to noninfectious causes, such as an SAH. Two retrospective studies [24, 25] found associations between the SIRS burden and worse outcomes in SAH, with SIRS incidence ranging from 69 to 85%. Although present in 82% of our patients, SIRS was not associated with a poor outcome after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective observational study showed early SIRS was associated with worse SAH clinical severity (Hunts and Hess grade) and radiographic severity (modified Fischer score) and total SIRS burden measured by number of SIRS criteria met was predictive of three-month poor outcome in SAH. 128 Whether SIRS simply reflects initial SAH severity or whether it exerts independent effects on SAH outcome is not yet known. In a preliminary SAH retrospective cohort study, having SIRS at hospital presentation was independently associated with worse GCS on presentation and higher in-hospital mortality.…”
Section: Clinical Features Of Systemic Inflammation and Immune Dysfunmentioning
confidence: 99%
“…In specific, IL-6, IL-10, and MIP1ß have recently been identified as an indicator of EBI using correlation network analysis in humans [46••]. Moreover, early platelet activation, systemic inflammation, and SIRS (systemic inflammatory response syndrome) are common in the early phase after SAH and associated with disease severity and poor functional outcome [47, 48•].…”
Section: Definitionsmentioning
confidence: 99%